2020
DOI: 10.1002/fsn3.1766
|View full text |Cite
|
Sign up to set email alerts
|

Chirality of the biomolecules enhanced its stereospecific action of dihydromyricetin enantiomers

Abstract: The present study explores the effect of chirality of the biological macromolecules, its functional aspects, and its interaction with other food components. Dihydromyricetin (DHM) is a natural novel flavonol isolated from the vine tea (Ampelopsis grossedentata) leaves. However, limited progress in enantiopure separation methods of such compounds hinder in the development of enantiopure functional studies. This study is an attempt to develop a simple, accurate, and sensitive extraction method for the separation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 36 publications
0
15
0
Order By: Relevance
“…The (+) DMY and (±) DMY in solidstate were distinguished using spectroscopic analyses, i.e., 1 H NMR and chiral HPLC [16]. Several separation and purification methods reported include high-speed countercurrent chromatography [48,49], supercritical fluid chromatography [50], recrystallization [17] found successful to yield homochiral DMY.…”
Section: Chiral Separationmentioning
confidence: 99%
See 1 more Smart Citation
“…The (+) DMY and (±) DMY in solidstate were distinguished using spectroscopic analyses, i.e., 1 H NMR and chiral HPLC [16]. Several separation and purification methods reported include high-speed countercurrent chromatography [48,49], supercritical fluid chromatography [50], recrystallization [17] found successful to yield homochiral DMY.…”
Section: Chiral Separationmentioning
confidence: 99%
“…For extraction, separation and purification of DMY from A. grossedentata leaves, several methods including reflux, ultrasound, microwave, supercritical fluid chromatography, high‐speed countercurrent chromatography, crystallization and microporous resin adsorption are commonly used alone or in combination. Whereas, for structural identification of DMY, proton nuclear magnetic resonance ( 1 H‐NMR), single‐crystal X‐ray diffraction (XRD), infrared radiation, UV‐Vis spectrum and Fourier‐transform infrared spectroscopy are used [13, 17, 38]. Identification of exact stereoisomer should be determined using techniques, such as chiral column chromatography and circular dichroism.…”
Section: Extraction Separation and Purificationmentioning
confidence: 99%
“…Previous research has shown that hydroxylation at the fifth and seventh sites is important for flavonol antibacterial activity against bacteria (Echeverría et al., 2017; Umair et al., 2020; Zapadka et al., 2019). Furthermore, another study examined the link between flavonoid structure and antibacterial properties, finding a similar hydroxylation site to be associated with antimicrobial activity (Farhadi et al., 2019) and antibiotic resistance (Abdelgader et al., 2018).…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that 2R, 3R‐dihydromyricetin (DHM), a flavonoid isolated from vine tea, had good inhibitory action against S. aureus (Umair et al., 2020). In terms of the structure–activity connection of flavonoids, very little research has been conducted on the role of the C‐ring in antibacterial activity (Cushnie & Lamb, 2011).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation